Association of rotator cuff degeneration and scapular anatomy with humeral head migration in rotator cuff arthropathy - Hannes E. Tytgat; Nazanin Daneshvarhasjin; Philippe Debeer; Jean Chaoui; Filip Verhaegen (Journal of Experimental Orthopaedics)
Abstract Purpose Rotator cuff tear arthropathy (RCTA) is characterised by humeral head migration (HHM). The exact pathogenesis of HHM is poorly understood, although rotator cuff (RC) failure and scapular anatomy are thought to play an important role. The aim of this study is to investigate the possible association between HHM and the quantitative aspects of scapular anatomy and RC degeneration. Methods We analysed computed tomography scans of 43 RCTA patients. RC fatty infiltration (FI) and atrophy, HHM, and both native and pathologic scapular anatomy were quantitatively assessed in three dimensions. Results Patients with superior HHM had a significantly higher critical shoulder angle (34° vs. 30°, p = 0.009), and FI of the supraspinatus (26% vs. 16%, p = 0.025) and infraspinatus (IS) (25% vs. 16%, p = 0.038) compared to patients without superior HHM. Patients with posterior HHM had a significantly more retroverted native (mean 10° vs. 6°; p = 0.002) and pathologic glenoid (mean 11° vs. 4°; p = 0.001) and a higher anterior axis length (mean 40 mm vs. 37 mm; p = 0.001) compared to patients without anteroposterior HHM. Multivariate regression analysis showed that the native glenoid version, anterior axis length and the volume (Vol) of IS divided by subscapularis (p = 0.01) were independent predictors of the magnitude of anteroposterior HHM, together explaining 41% of its variance. Conclusion In RCTA, degeneration of the posterosuperior RC and acromion morphology seems to be associated with superior HHM, while in the glenoid version, the rotational alignment of the coracoacromial complex and an imbalance in FI and muscle Vol in the transverse force couple seems to be associated with anteroposterior HHM. Level of Evidence Level III.